THE INFLUENCE OF WOMEN’S LEADERSHIP ON EMPLOYEE ENGAGEMENT MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AT DIGITAL AGENCIES - Amelia, Syafira Widya; Mulyono, Mulyono (UTSAHA: Journal of Entrepreneurship, 2024)
Leadership roles in companies have a huge influence on employee retention and voluntary behavior. Leader has a very crucial role in building relationships between employees and the company, since employee is an important element of a company. Women leaders are frequently associated with leadership styles that emphasize collaboration, understanding, empathy, and the development of strong interpersonal relationships, all of which can influence employee engagement. This research aims to analyze the influence of women’s leadership on employee engagement mediated by organizational citizenship behavior. The research investigates this relationship at digital agencies using quantitative descriptive approach and a cross sectional method. Involving 54 respondents, consisting of employees and clients of the company, this research employs structural equation modeling partial least square (SEM PLS). The test results indicate that women’s leadership has a positive and significant influence on employee engagement. Furthermore, organizational citizenship behavior is positively and significantly impacted by women in leadership roles. Nonetheless, there is no moderating effect of corporate citizenship behavior on the connection among staff involvement and women in leadership.